2017
DOI: 10.1038/srep45569
|View full text |Cite
|
Sign up to set email alerts
|

Enteric glial cells counteract Clostridium difficile Toxin B through a NADPH oxidase/ROS/JNK/caspase-3 axis, without involving mitochondrial pathways

Abstract: Enteric glial cells (EGCs) are components of the intestinal epithelial barrier essential for regulating the enteric nervous system. Clostridium difficile is the most common cause of antibiotic-associated colitis, toxin B (TcdB) being the major virulence factor, due to its ability to breach the intestinal epithelial barrier and to act on other cell types. Here we investigated TcdB effects on EGCs and the activated molecular mechanisms. Already at 2 hours, TcdB triggered ROS formation originating from NADPH-oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…Furthermore, we observed that a reactive EGC phenotype can also have detrimental effects on the EGCs as shown by increased DNA fragmentation and cell death through the increased inflammation and ROS generated. This ultimately may result in programmed cell death in glia by pyroptosis or apoptosis as shown elsewhere (Macchioni et al, 2017). The general loss in enteric glia could lead to suboptimal functioning of enteric neurons and even enteric neuropathy (Bassotti et al, 2018).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, we observed that a reactive EGC phenotype can also have detrimental effects on the EGCs as shown by increased DNA fragmentation and cell death through the increased inflammation and ROS generated. This ultimately may result in programmed cell death in glia by pyroptosis or apoptosis as shown elsewhere (Macchioni et al, 2017). The general loss in enteric glia could lead to suboptimal functioning of enteric neurons and even enteric neuropathy (Bassotti et al, 2018).…”
Section: Discussionmentioning
confidence: 77%
“…Studies have showed that NADPH oxidases are activated in response to pathogenic stimuli in human EGC (Macchioni et al, 2017). We found that treatment of EGC with LPS or HMGB1 significantly increased their expression of NOX-2 (Figures 11A–D) ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our previous study indicated that mitochondrial function was associated with ADR-induced apoptosis (12). It is well known that mitochondria are essential for oxidative phosphorylation and generation of reactive oxygen species during ATP production (35). Zhu et al reported that the strong apoptotic response in ADR-treated cells is associated with increased mitochondrial damage and ROS production (36).…”
Section: Discussionmentioning
confidence: 90%
“…It was demonstrated that TcdB stimulates morphological alteration and apoptosis in EGCs in vitro [98,103]. TcdB-induced apoptosis of EGCs involves the NADPH oxidase/ ROS/JNK/caspase-3 signaling pathway independently of the mitochondrial pathway [103]. In addition, TcdB induces senescence in EGCs.…”
Section: Colitis By Clostridioides Difficilementioning
confidence: 99%